Motivating factors influencing business among youth in Malaysia / Sharifah Zannierah Syed Marzuki ... [et al.] - Syed Marzuki, Sharifah Zannierah; Abdul Kadir, Mohd. Ali Bahari; Buyong, Siti Zahrah; Junid, Junainah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
As Malaysia continues to grow economically, youth entrepreneurship has become a vital factor in ensuring a brighter future for the nation. Entrepreneurship is seen as not only the solution to unemployment, but also fundamental in nurturing young people to unleash their potential to the fullest. In order to encourage young generation to embark on entrepreneurship, it is important to comprehend what motivates young entrepreneurs to start their own business so as to help relevant agencies and interested parties to design suitable entrepreneurship programmes for the segment. This paper presents the results of focus group discussion with young entrepreneurs from three different ethnics in Malaysia which suggest that motivating factors influencing young entrepreneurs are monetary and non-monetary reward, related experience, personal background, passion, networking opportunity, encouragement from influential family members and business influence from colleagues.